Advance in Post-harvest Preservation Technology - Cefola, Maria; Pace, Bernardo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fruits and vegetables are important sources of nutrients, such as vitamins, minerals, and bioactive compounds, and provide many health benefits. However, due to non-optimal post-harvest management, large quantities of fresh or fresh-cut fruits and vegetables experience a decline in their quality and nutritional value before they reach the consumer. This Special Issue covers technologies for the harvesting, handling, and storage of vegetables, including storage strategies such as active packaging, edible coatings, the application of nanotechnology in the post-harvest of vegetable crops, and others, with the aim of improving the shelf-life of fresh and fresh-cut fruits and vegetables.